2013
DOI: 10.1007/s10815-013-0031-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of male germline stem cells from piglets

Abstract: Purpose To study the effects of serum and growth factors on propagation of porcine male germline stem cells (MGSCs) in vitro and develop a culture system for these stem cells. Methods Fresh testicular cells from neonatal piglets were obtained by mechanical dissociation and collagenase-trypsin digestion. After differential plating, non-adhering cells were cultured in media supplemented with different concentrations of serum (0, 1 %, 2 %, 5 %, 10 %). After 10 days of primary culture, the cells were maintained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 31 publications
(42 reference statements)
2
35
0
Order By: Relevance
“…The authors evaluated the effects of growth factors based on the number of colonies of SSC-like, and expression level of SSC markers and suggest that FGF can impede successful derivation of porcine SSCs from neonate pig testis (Goel et al 2009). Update, the effects of cytokines and growth factors on porcine mGSCs were not clear (Goel et al 2009;Zheng et al 2013). In the present study, the pmGSCs have been cultured up to 14 passages for over two months, while still maintained a typical morphology to mouse and human GSCs, indicating that our cultural system could simulate the cellular niche in seminiferous tubules that maintained the proliferation and differentiation of mGSCs in vitro.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…The authors evaluated the effects of growth factors based on the number of colonies of SSC-like, and expression level of SSC markers and suggest that FGF can impede successful derivation of porcine SSCs from neonate pig testis (Goel et al 2009). Update, the effects of cytokines and growth factors on porcine mGSCs were not clear (Goel et al 2009;Zheng et al 2013). In the present study, the pmGSCs have been cultured up to 14 passages for over two months, while still maintained a typical morphology to mouse and human GSCs, indicating that our cultural system could simulate the cellular niche in seminiferous tubules that maintained the proliferation and differentiation of mGSCs in vitro.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies demonstrated that several pluripotent/multipotent germline stem cells have been established and characterized by different research groups using various protocols, and murine and human male GSCs can be cultured for long periods and retain the capacity to differentiate into multiple cell types in the presence of serum or feeder cells in vitro. Recently, porcine, goat and bovine mGSCs were cultured and characterized, and these cells shared similar characteristics of ES cells and GSCs (Kanatsu-Shinohara et al 2008;Goel et al 2009;Kuijk et al 2009;Hua et al 2011;Zeng et al 2013;Zheng et al 2013;Park et al 2014). However, the methods available for isolating SSCs and mGSCs from porcine testicular cells have a low efficiency of cell separating, and it is difficult to establish a stable livestock mGSCs line Zheng et al 2013;Park et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations